EFEKTIVITAS PROGRAM REHABILITASI YAYASAN REHABILITASI RUMAH UMMI DI MASA COVID-19 - Br Banjar Nahor, Angelica Theresia Adelia; Mia Aulina Lubis; Malida Putri (Yayasan Literasi Sains Indonesia, 2022)
The drug problem in Indonesia is still something urgent and complex. Evidenced by the high cases of abusers or drug addicts and the increasing disclosure of drug crimes that are increasingly diverse patterns and more and more syndicate networks. Drug use is not onlymentally damaging but also damages the user's body. Consuming drugs can weaken the body's immunity which serves to protect the body from infections of various viruses and bacteria, including Covid-19. Regular and long-term use of narcoba has the potential to have health impacts on the lungs, heart, blood vessels, brain, and other organs. Rehabilitation is a way to help drug addicts by treating and rehabilitating these victims so that they can return to carry out social functions properly that have previously been disrupted, so that they can return to the community, work and study properly. The purpose of this study is to find out the effectiveness of the Yayasan Rehabilitasi Rumah Ummi rehabilitation program using 5 indicators of Sutrisno's program effectiveness theory (Program Understanding, Accuracy of Targets, Timeliness, Achieving Goals, and Real Change) during the Covid-19 period. The methods carried out in this study are descriptive research methods with a qualitative approach. The key informants in the study were Program Manager, the main informants in this study were three residents, and additional informant in this study were counselor. The results of this study show that the implementation of the Rehabilitation Program of the Yayasan Rehabilitasi Rumah Ummi during the Covid-19 period is effective. The implementation of the rehabilitation program has been carried out well even though there are still weaknesses in the implementation of the program becausethere are eliminated outdoor activities due to the Covid-19 pandemic.